If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -2) * 9 = 2(8x + 7) Reorder the terms: 5(-2 + 4x) * 9 = 2(8x + 7) Reorder the terms for easier multiplication: 5 * 9(-2 + 4x) = 2(8x + 7) Multiply 5 * 9 45(-2 + 4x) = 2(8x + 7) (-2 * 45 + 4x * 45) = 2(8x + 7) (-90 + 180x) = 2(8x + 7) Reorder the terms: -90 + 180x = 2(7 + 8x) -90 + 180x = (7 * 2 + 8x * 2) -90 + 180x = (14 + 16x) Solving -90 + 180x = 14 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -90 + 180x + -16x = 14 + 16x + -16x Combine like terms: 180x + -16x = 164x -90 + 164x = 14 + 16x + -16x Combine like terms: 16x + -16x = 0 -90 + 164x = 14 + 0 -90 + 164x = 14 Add '90' to each side of the equation. -90 + 90 + 164x = 14 + 90 Combine like terms: -90 + 90 = 0 0 + 164x = 14 + 90 164x = 14 + 90 Combine like terms: 14 + 90 = 104 164x = 104 Divide each side by '164'. x = 0.6341463415 Simplifying x = 0.6341463415
| 15+7x-2x^2=0 | | 24-(1+1)^4/4 | | by^2+11xy+4x^2=0 | | 0.25x+x=100 | | 4x-4=4(x+9) | | 0.25*x+x=100 | | 36*6-2+a=24 | | 3004-x=7806 | | 5x/18-4=x/6+10 | | 36/6-2+a=24 | | 2x/5=7 | | 18/2*9 | | x^3+4x^2+2x-1=0 | | 2x+8x+5x=13 | | 18/2x9 | | t+9=t-3(2t+5) | | 10x=15x+2 | | 4x+s=14 | | 1-(y+2)=-14+(y+3) | | 8y-12y=-10-14 | | 2v=v+6(v-5) | | -14-29=13+2x-14 | | a(a+3)=12+4a | | -3(x+2)-45=8-35 | | d^2-5d-50=0 | | 23x+8-25x=4-6 | | 7x+14-6x=-8-11 | | 67y=22(3y+2) | | 12x=6-(-18) | | 12x=6(-18) | | d^2=5d+50 | | 9-4x=7x+24 |